A Ku-Band SIW six-port - Tan Gan Siang; Siti Zuraidah Ibrahim; Mohd Nazri A. Karim; Aliya A. Dewani; Mohammad Shahrazel Razalli (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper shows a compact fully integrated six-port Substrate Integrated Waveguide (SIW) operating at Ku-Band frequency range. The SIW six-port is formed by combining two SIW power dividers and two SIW couplers, having the benefit of no additional termination is required as this topology has no excessive port. To achieve the optimized design of the six-port, both of the key components; power divider and coupler are primarily designed, fabricated, and measured individually. Y-junction topology is employed on the power divider structure to achieve a compact size. In turn, the coupling coefficient of the two output ports of the SIW coupler are improved by shifting the position of a row of several vias located at the side wall center closer to the side wall. The simulated six port performance provides an advantage of wide bandwidth within Ku-Band across 13 to 17 GHz with a return loss better than 12 dB and transmission coefficient of 7±1.5 dB. The simulated and measured results show good agreement thus validating the prototype. The SIW six-port can find its application in designing a six-port.